NILAI DIAGNOSTIK SKOR KLINIS DIBANDINGKAN DENGAN BIOPSI PATOLOGI ANATOMI DALAM MENDIAGNOSIS PASIEN KARSINOMA NASOFARING - Dini Desviana Rahmayanti; Ika Kustiyah Oktaviyanti; Istiana Istiana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2015)
Nasopharyngeal malignancy is the most commonly found among head and neck malignancies. Generally, nasopharyngeal cancer, has a good prognosis if it is detected as soon as possible. It is very important to diagnose it earlier because survival rate can be longer if therapy is given early. This study aims to determine the diagnostic value of clinical scores compared with histopathology biopsy to diagnose nasopharyngeal carcinoma in patients of RSUD Ulin Banjarmasin in the period 2012-2014. Subjects of this study were patients of RSUD Ulin Banjarmasin Hospital which is suspected nasopharyngeal carcinoma, who have examined the clinical symptoms by history and physical examination, had been registered in the medical record, and had been examined with histopathology biopsy. Data of clinical examination and histopathology biopsy from each sampel were collected for clinical symptom scores were analyzed according to get sensitivity value, specifity value, positif predictive value, and negative predictive value.Total subject of this research was 30. In this study, a minimum clinical score to lead to a nasopharyngeal malignancy that if found clinical score of 4, with a sensitivity, specifity, positive predictive value , and negative predictive value of 75%, 83.33%, 94.74%, 45.45% respectively. Clinical characteristics have high sensitivity and specifity to diagnose nasopharyngeal carcinoma. Keywords: diagnostic value, clinical scores, nasopharyngeal carcinoma